PENGARUH FAKTOR-FAKTOR MAKROEKONOMI TERHADAP ISLAMIC HUMAN DEVELOPMENT INDEX (IHDI) DI INDONESIA TAHUN 2013-2017 - Siti Rochmah; Raditya Sukmana (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The human development Index (HDI) established by UNDP, might be the most comprehensive approach but is not fully compatible and sufficient for measuring development in Muslim countries, because HDI measurements are not based on Islamic perspective. The HDI is unable to capture the religious and ethical perspective of socio-economic development in Muslim countries. human development and welfare of human being is an ultimate goal in the whole Islamic framework. Therefore, came a measurement called Islamic Human Development Index (I-HDI) as a holistic and comprehensive index for human development derived from the five dimensions of Maqāṣid al-Sharīʿah: religion (dīn), life (nafs), intellect (ʿaql), family (nasl) and wealth (māl). This study aims to determine the effect of macroeconomics factor on Islamic human development Index In Indonesia. The analysis technique used is multiple linearregression. The findings show that unemployment and poverty levels have a significant effect on IHDI, while GRDP does not affect IHDI. In addition, the results show that there are differences in ranking between HDI and IHDI. Some Provinces get IHDI acquisition which is quite low, which is below 50% which can be seen in NTT, NTB, and Papua Provinces. While the other provinces get good IHDI acquisition so that there is still a wealth of prosperity in provinces in Indonesia.Keywords: Economic Development, Maqashid Shariah, Human Development, Islamic Human Development IndexREFERENCESAhmad, Ausaf, 2000. Economic DevelopmentIn Islamic Perspective Revisited Review Of Islamic Economic.Amin, Dkk.,A New Comprehensive Approach to Measuring Human Development.Department of Economic, International Islamic UniversityMalaysia.Anto, M. Hendrie. 2009.Introducing an Islamic Human Development Index (IHDI) to Measure Development in OIC Countries.Islamic Economic Studies, Vol. 19 No.2.Rama, Ali, dan Burhanuddin Yusuf. 2019. Construction of Islamic Human Development Index (IHDI). Islamic Economic Studies, Vol. 32 No.1.